Development of Small‐Molecule Cryptochrome Stabilizer Derivatives as Modulators of the Circadian Clock. Issue 9 (14th July 2015) - Lee, Jae Wook; Hirota, Tsuyoshi; Kumar, Anupriya; Kim, Nam‐Jung; Irle, Stephan; Kay, Steve A.
Abstract Small‐molecule probes have been playing prominent roles in furthering our understanding of the molecular underpinnings of the circadian clock. We previously discovered a carbazole derivative, KL001 (N‐(3‐(9H‐carbazol‐9‐yl)‐2‐hydroxypropyl)‐N‐(furan‐2‐ylmethyl)methanesulfonamide), as a stabilizer of the clock protein cryptochrome (CRY). Herein we describe an extensive structure–activity relationship analysis of KL001 derivatives leading to the development of a highly active derivative: 2‐(9H‐carbazol‐9‐yl)‐N‐(2‐chloro‐6‐cyanophenyl)acetamide (KL044). Subsequent 3D‐QSAR analysis identified critical features of KL001 derivatives and provided a molecular‐level understanding of their interaction with CRY. The electron‐rich carbazole, amide/hydroxy linker, sulfonyl group, and electron‐withdrawing nitrile moieties contribute to greater biological activity. The hydrogen bonding interactions with Ser394 and His357 as well as stronger CH–π interactions with Trp290 make KL044 a better binder than KL001. KL044 lengthened the circadian period, repressed Per2 activity, and stabilized CRY in reporter assays with roughly tenfold higher potency than KL001. Altogether, KL044 is a powerful chemical tool to control the function of the circadian clock through its action on CRY.